How Determinants of Employee Innovation Behavior Matter During the COVID-19 Pandemic: Investigating Cross-Regional Role via Multi-Group Partial Least Squares Structural Equation Modeling Analysis - Cao, Caixia; Peng, Michael Yao-Ping; Xu, Yan (Frontiers in Psychology, 2022)
The COVID-19 pandemic cropping up at the end of 2019 started to pose a threat to millions of people’s health and life after a few weeks. Nevertheless, the COVID-19 pandemic gave rise to social and economic problems that have changed the progress steps of individuals and the whole nation. In this study, the work conditions for employees from Taiwan, Malaysia and Chinese mainland are explored and compared, and the relationship between support mechanisms and innovation behaviours is evaluated with the view of the social cognitive career theory. This study adopts the cross-sectional survey and purposive sampling to collect questionnaires. A total of 623 copies of questionnaire from Taiwanese, 440 copies from Malaysians and 513 copies from mainlanders were collected in this study to compare the three groups in developing employees’ innovation behaviors. Smart-PLS for PLS-SEM was applied in the structural model to conduct a verification of the hypotheses and comparative analysis in this study. According to the findings, compared with employees from Chinese mainland, the Taiwanese and Malaysian samples show more significant paths with regard to employee employability, innovation behaviour, prior knowledge, perceived organizational support, self-efficacy and job performance. Our results will offer more insights and advices concerning theories of human resource.